Polarizability effect in strong-field ionization: Quenching of the low-energy structure in C60 - Lai, Yu Hang; Blaga, Cosmin I.; Xu, Junliang; Fuest, Harald; Rupp, Philipp; Kling, Matthias F.; Agostini, Pierre; Dimauro, Louis F. (Physical Review A, 2018)
The low-energy photoelectron spectra from strong-field ionization of C60 fullerenes and noble gases (xenon and krypton) with 3μm laser pulses are measured and compared. It is found that the low-energy structure (LES), a universal spikelike feature in the strong-field limit of atoms and small molecules, is significantly suppressed in the C60 photoelectron distribution. We propose that the large polarizability of the C60 core disrupts the corresponding electron trajectories. In particular, the induced dipole force repels the electron, which opposes the focusing and bunching due to the Coulomb potential that is responsible for the LES, thus leading to its reduction.
CRIS-Team Scopus Importer:2023-04-20